Price as a Signal of Product Quality: Some Experimental Evidence*. (3rd July 2014) - Mastrobuoni, Giovanni; Peracchi, Franco; Tetenov, Aleksey
Abstract We use experimental data to disentangle the signaling and budgetary effects of price on wine demand. The experimental design allows us to isolate the two effects in a simple and intuitive way. The signaling effect is present and nonlinear: it is strongly positive between 3 euros and 5 euros and undetectable between 5 euros and 8 euros. We find a similar nonlinear price–quality relationship in a large sample of wine ratings from the same price segment, supporting the hypothesis that taster behavior in the experiment is consistent with rationally using prices as signals of quality. Price signals also have greater importance for inexperienced (young) consumers. (JEL Classification: D11, D12, D82)